2005
DOI: 10.1002/jctb.1204
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bacillus thuringiensis‐based biopesticides in batch and fed batch cultures using wastewater sludge as a raw material

Abstract: Bacillus thuringiensis subsp kurstaki was grown in batch and fed batch cultures using wastewater sludge as a raw material. A simple fed batch strategy based on dissolved oxygen measurement during the fermentation cycle was developed in this work. It was established that while shifting the process strategy from batch to fed batch, the maximum spore concentration was increased from 5.62 × 10 8 to 8.6 × 10 8 colony forming units per cm 3 and resulted in an increase of entomocidal activity from 13 × 10 9 to 18 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…Furthermore, these high μ m values (around 1 h −1 ) showed that the cultures were not under any other nutritional or environmental limitation, including oxygen, during the first 4-5 h of fermentation, the time they were calculated. Similar or even smaller μ m values were previously described for other Bt strains under culture conditions that were not considered limiting for growth (Flores et al 1997;Rowe et al 2003;Yezza et al 2005;López-Y-López and De La Torre 2005). For all conditions evaluated, it was also observed that the exponential phase was followed by a period of non-exponential growth, where cell growth curves presented a linear profile.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Furthermore, these high μ m values (around 1 h −1 ) showed that the cultures were not under any other nutritional or environmental limitation, including oxygen, during the first 4-5 h of fermentation, the time they were calculated. Similar or even smaller μ m values were previously described for other Bt strains under culture conditions that were not considered limiting for growth (Flores et al 1997;Rowe et al 2003;Yezza et al 2005;López-Y-López and De La Torre 2005). For all conditions evaluated, it was also observed that the exponential phase was followed by a period of non-exponential growth, where cell growth curves presented a linear profile.…”
Section: Resultssupporting
confidence: 84%
“…Higher DO level also led to a positive impact on spore production (Table 1), which can be explained by increasing growth rates with the enhancement of DO concentrations. Fast growing cells carry higher energy, which leads to a higher sporulation (Yezza et al 2005). Quantitatively, the differences in spore counts are in agreement with those verified for Bti by Kraemer-Schafhalter and Moser (1996) using similar DO levels, but diverged from those obtained by Avignone-Rossa et al (1992), who found analogous spore counts with different DO values.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Thus, biotechnological products such as biopesticides (Yezza et al 2005), biochemicals such as lactic acid (Ma et al 2014), and biofuels such as biohydrogen (Ting and Lee 2007) have been produced using WAS as a nutrient source for the involved microorganisms. Cheung and Anderson (1997) tried to produce ethanol from the cellulose content of primary sludge of WWTPs, via simultaneous saccharification and fermentation (SSF).…”
Section: Introductionmentioning
confidence: 99%